Validação e análise da precisão da versão em português do Needs of Parents Questionnaire Validation and reliability analysis of the Portuguese language version of Needs of Parents Questionnaire - Pedro L. Ferreira; Elsa Melo; Gina Reis; Débora F. Mello (Elsevier, 2010)
OBJETIVO: Descrever os procedimentos para a validação e análise de precisão da versão em português do Needs of Parents Questionnaire em contexto de hospitalização pediátrica em Portugal. MÉTODOS: Estudo descritivo com base em procedimentos para adaptação cultural e linguística de instrumentos de medição em saúde. A validação foi efetuada em uma amostra de 870 acompanhantes de crianças hospitalizadas em serviços de pediatria de quatro hospitais de Portugal, com idades compreendidas entre 2 dias de vida e 18 anos. A validade de conteúdo foi garantida por dois testes de compreensão realizados separadamente com pais de crianças hospitalizadas e com profissionais de saúde. A confiabilidade da versão em português foi avaliada através do teste de reprodutibilidade e determinação da coerência interna. RESULTADOS: Os resultados dos testes de compreensão e de coerência interna, obtidos pelo coeficiente alfa de Cronbach, são idênticos aos do autor original e satisfatórios para três subescalas, o que nos permite afirmar que o questionário tem propriedades psicométricas adequadas para a medição das necessidades dos pais. O questionário foi bem recebido pelos pais das crianças, que valorizam todas as necessidades, destacando a necessidade de confiar nos cuidados de saúde que são prestados à criança quando não estão presentes, a necessidade de ser confiável e as necessidades de informação. CONCLUSÕES: O questionário mostrou ser um instrumento de medição válido e preciso na avaliação das necessidades dos pais durante a hospitalização das crianças. A versão em português do Needs of Parents Questionnaire se encontra validada. OBJECTIVE: To describe the procedures followed for the validation and reliability analysis of the Portuguese version of the Needs of Parents Questionnaire in the context of pediatric hospitalization in Portugal. METHODS: This is a descriptive study based on procedures for the cultural and linguistic adaptation of health measurement tools. The validation was performed on a sample of 870 parents of hospitalized children in pediatrics departments from four hospitals in Portugal, with ages ranging from 2 days to 18 years. Content validity was assured by two cognitive debriefing meetings, separately organized with parents and staff. The reliability of the Portuguese version was assessed through reproducibility tests and internal consistency computation. RESULTS: Using Cronbach's alpha, results from the cognitive debriefing and internal consistency scores were similar to those obtained by the authors of the original version and good for the three subscales, allowing us to state that the questionnaire has the adequate psychometric properties to measure parents' needs. It was well accepted by parents, who valued all needs, especially the need to trust the care provided to their child when they are not present, as well as the need to be trusted and the need for information. CONCLUSIONS: The questionnaire proved to be a valid and reliable measurement instrument to assess the needs of parents during their pediatric hospitalizations. The Portuguese version of the Needs of Parents Questionnaire has been validated.